2016
DOI: 10.1371/journal.pone.0148382
|View full text |Cite
|
Sign up to set email alerts
|

The Principal Forces of Oocyte Polarity Are Evolutionary Conserved but May Not Affect the Contribution of the First Two Blastomeres to the Blastocyst Development in Mammals

Abstract: Oocyte polarity and embryonic patterning are well-established features of development in lower species. Whether a similar form of pre-patterning exists in mammals is currently under hot debate in mice. This study investigated this issue for the first time in ovine as a large mammal model. Microsurgical trisection of unfertilized MII-oocytes revealed that cortical cytoplasm around spindle (S) contained significant amounts of total maternal mRNAs and proteins compared to matched cytoplast hemispheres that were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(131 reference statements)
3
9
0
Order By: Relevance
“…In the present study, we confirm the presence and a comparable distribution of the three different cell allocation patterns in mouse blastocysts irrespective of mouse strain or embryo cryopreservation at 1-cell stage. These resuls are also in agreement with those previously reported in mouse, bovine and ovine embryos ( Hosseini et al 2016 , Sepulveda-Rincon et al 2016 ). Embryo biopsy at the 8-cell stage, whether the biopsied cell is stained or not stained (data not shown), does not seem to alter the cell allocation patterns in mouse embryos similar to what we have previously reported in bovine embryos ( Sepulveda-Rincon et al 2016 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we confirm the presence and a comparable distribution of the three different cell allocation patterns in mouse blastocysts irrespective of mouse strain or embryo cryopreservation at 1-cell stage. These resuls are also in agreement with those previously reported in mouse, bovine and ovine embryos ( Hosseini et al 2016 , Sepulveda-Rincon et al 2016 ). Embryo biopsy at the 8-cell stage, whether the biopsied cell is stained or not stained (data not shown), does not seem to alter the cell allocation patterns in mouse embryos similar to what we have previously reported in bovine embryos ( Sepulveda-Rincon et al 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is still unclear if mammalian embryos are pre-patterned or the presence of stochastic development is just a reflex of the great plasticity of mammalian embryos. Research performed on cell allocation patterns suggest that it might be a common characteristic during pre-implantation embryo development of different mammalian species ( Park et al 2009 , Hosseini et al 2016 , Sepulveda-Rincon et al 2016 ). However, there is a lack of evidence on the mechanism(s) leading to these cell allocation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Such a gradient has been described for LEPTIN and STAT3 in mouse and human oocytes 50 . Western blot analysis of bisected sheep oocytes revealed that specific maternal proteins, including NANOG, are distributed asymmetrically 51 . In mice, however, Nanog is not transcribed in early embryos until the 8-cell stage 52 , thereby excluding the possibility that a different maternal legacy of Nanog mRNA in the sister two-cell blastomeres would account for the discordant sizes of the EPI compartments of the MZ blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…These actin-filled hairlike projections greatly enlarge the contact area and decrease the repulsion between the two juxtapositioned membranes [49]. In many animal species, sperms have a preferential entry point [50][51][52]. In mouse, rat, and hamster eggs, sperm do not fuse with the microvilli-free Fig.…”
Section: Sperm-egg Associationmentioning
confidence: 99%